Indo-Bhutan relations through prism of history - Rajput, Madhu (New Delhi, 2011)
No other countries can boast of closeness as India and Bhutan claim. The book is an attempt to understand the spirit behind the relations in its entirety beginning from early times to present day. Notwithstanding the tumultuous changes political, social and economic have taken place in the tiny Himalayan kingdom of Bhutan, the relations have strengthened and India has played an important role in Bhutan's emergence from isolation to the international arena. The book traces its journey from its nascent times to the developing nation it is today with per capita income which is the highest in South Asia.
Keywords: India-Foreign relations-Bhutan